Towards housing policies that consider household’s preferences: estimating the demand for housing attributes in Chile - Lopez, Esteban; Paredes, Dusan (International Journal of Strategic Property Management, 2018)
Understanding household preferences for housing attributes is imperative for developing countries after years of housing policies that failed mostly due to the mismatch between housing solutions and needs. This paper provides income and price elasticity estimates of the demand for housing attributes as an indicator to measure how households perceive housing attributes (necessities or luxuries). These metrics are important because they allow evaluating previously national-level housing policies as well as suggesting new paths of action that are in accordance to households’ preferences. The study focuses on Chile because its influential role in designing housing policies in other developing countries (Gilbert, 2002). Using five cross-section household surveys from 2000–2011, our results suggest that Size and Location are perceived as basic necessities. Contrarily, Quality and Housing Features are considered luxury goods. Size and Location are more price-inelastic than other attributes. These results are consistent across regions, and suggest that households prefer larger and better-located houses.